Literature Review On Factors Affecting Patient Satisfaction With Pharmacy Services In Indonesia - Septi Purnama Sari; Magfiroti Fitri (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to analyze the factors influencing patient satisfaction with pharmacy services in Indonesia through a literature review. A total of 17 relevant articles were systematically reviewed to identify patterns of findings. The results indicate that patient satisfaction is influenced by comprehensive drug information, fast service waiting times, the attitude and communication skills of pharmacy staff, and service quality based on the SERVQUAL dimensions. Improving these factors is essential to achieving patient-oriented pharmaceutical services and supporting appropriate drug use and optimal therapeutic outcomes.